Piriformis Syndrome in Fibromyalgia: Clinical Diagnosis and Successful Treatment - Md Abu Bakar Siddiq; Moshiur Rahman Khasru; Johannes J. Rasker (Case Reports in Rheumatology)
Piriformis syndrome is an underdiagnosed extraspinal association of sciatica. Patients usually complain of deep seated gluteal pain. In severe cases the clinical features of piriformis syndrome are primarily due to spasm of the piriformis muscle and irritation of the underlying sciatic nerve but this mysterious clinical scenario is also described in lumbar spinal canal stenosis, leg length discrepancy, piriformis myofascial pain syndrome, following vaginal delivery, and anomalous piriformis muscle or sciatic nerve. In this paper, we describe piriformis and fibromyalgia syndrome in a 30-year-old young lady, an often missed diagnosis. We also focus on management of the piriformis syndrome.